A group test of intelligence for the deaf - Du Toit, Jozua Malherbe (Department of Psychology, 2016)
A short survey of previous attempts at providing intelligence tests suitable for the deaf is made, and the most important of these tests are critically examined. It is shown that the few existing group tests for the deaf are quite inadequate and unsatisfactory, a fact which might possibly account for the discrepancy in the findings of different investigators, and in the results of different tests. The need for a better group test of intelligence for the deaf is emphasized and stated as the aim of the present investigation. For such a test to be satisfactory it would have to comply with certain principles, based on a priori considerations and on actual experience and acquaintance with the deaf. These conditions are briefly as follows: The test should presuppose as little acquired knowledge (such as language in any form) as possible; it should be possible to give the necessary instructions by pantomime only; it should fall within the proper range of difficulty; no speed tests should be included; abundant practice material should be provided; subtests should consist of many items; the material should capture and retain the interest of deaf children. Fifteen tests brought together for the purpose of a preliminary selection, are briefly described. The results of the application of these tests to a group of deaf pupils are considered, the merits of the different tests in practice are discussed and the reasons for discarding some of them are given. The ten tests retained were applied to a random sample of twenty percent of all normal children of ages ten, eleven and twelve years in eight schools, together with a criterion test.